HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PERSONAL HYGIENE SAATMENSTRUASI PADA REMAJA PUTRI - Husni, Husni (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
One of the effects is not maintaining hygiene during menstruation is able to hitkankes Rahim neck (cervical). Based on data from the World Health Organization (WHO),cervical cancer is the second most cancer in women aged 15-45 years after breast cancer. Noless than 500,000 new cases with 280,000 patient deaths occur each year worldwide.Indonesia was ranked first by the victims died at least 555 women per day and 200,000women annually. This study aims to determine the correlation between knowledge andattitude towards personal hygiene during menstruation action at SMAN 2 Bengkulu City. Thisresearch is descriptive analytic. The number of respondents 84 people with a samplingtechnique that stratified random sampling. Presentation of data is done by using a frequencydistribution table. The collection of data taken using a questionnaire. The data were analyzedusing univariate and bivariate analysis with Chi-Square.The results showed that therespondents are classified as good knowledge of (54.8%), attitude unfavorabel or does notsupport (53.6%), and the biggest acts (52.4%) is good. From the bivariate analysis were foundno correlation between knowledge against acts of personal hygiene during menstruation (p =0.794), and no relation attitude towards personal hygiene actions during menstruation (p =0.975).Required role of schools, educators, parents to be more proactive in enhancingknowledge and useful information about the process of menstruation and how to maintainhygiene during menstruation.